PERAN MEDIASI KEPUASAN KERJA DALAM PENGARUH WORK FAMILY CONFLICT DAN TURNOVER INTENTION PADA KARYAWAN WANITA - Tariana, I Wayan Aditya; Wibawa, I Made Artha (E-Jurnal Manajemen, 2016)
The analysis showed that the work family conflict and significant positive effect on turnover intention. Work family conflict and significant negative effect on job satisfaction. Job satisfaction and significant negative effect on turnover intention. The study also proved that job satisfaction mediates work family conflict towards a female employee turnover intention in PT. Bank Rakyat Indonesia (Persero) Tbk. London Branch. This research was carried out on female employees of PT. Bank Rakyat Indonesia (Persero) Tbk. London Branch. The purpose of this study was to determine the mediating role of job satisfaction in effect between work family conflict and turnover intention on female employees at PT. Bank Rakyat Indonesia (Persero) Tbk. London Branch. Samples taken as many as 103 respondents. The samples in this study using proportional random sampling technique. The data collection is done by distributing questionnaires to measure 11 question items. The analysis technique used is Path anaylsis. The bank should consider the level of work family conflict and job satisfaction felt by female employees. It is intended that the female employee has not thought related to the company's desire turnover intention.
Keywords: work family conflict, job satisfaction, turnover intention